(untitled) (Research, Society and Development, 2021)
Palliative care is a measure of care adopted from the moment when the possibility of a cure for the patient no longer exists. Nursing has a fundamental role in this process, offering comfort and quality of life to the child. The aim of this study was to understand the palliative approach of the pediatric nursing team. This is an integrative bibliographic review, based on scientific publications indexed in the databases of Latin American & Caribbean Health Sciences Literature (LILACS), Brazilian Nursing Database (BDENF), MEDLINE, via Virtual Health Library (VHL) and Scientific Electronic Library Online (SciELO), from 2015 to 2020. The analysis of the data was performed using the theme of data characterization, through which two categories emerged: “Approaches adopted by nursing in pediatric patients in palliative care” and “Team coping strategies in the face of situations experienced in the palliative care process”. The studies show the importance of the role played by nursing in this process, as well as, the difficulties that are encountered by the team and by the families that experience these situations, hence, in addition to assistance, nursing is a support network, support for patients and their families.